Correlation Between Quality of Life and Family Support with Stroke Incidence - Ixora, Ixora; Wulandari, Dewi; Tunik, Tunik (Health Access Journal, 2026)
Stroke not only affects the sufferer but also affects family life. This situation is further complicated when only one family member is caring for the stroke patient. The purpose of this study was to determine the correlation between quality of life and family support and stroke incidence. The study design was correlational with a cross-sectional approach. The sample was taken using a saturated sampling technique. The research instruments were observation to measure the incidence of stroke and questionnaires to measure the quality of life and family support, data analysis using the contingency coefficient test technique. The results of the study showed that most of the respondents, namely 28 (73.7%) had a quality of life in the good category, half of the respondents, namely 19 (50%) had family support in the sufficient category and the other half, namely 19 (50%) had family support in the good category, most of the respondents, namely 27 (71.1%) were non-hemorrhagic stroke. There is correlation between quality of life with incidence of stroke in the Bandung, because statistical test results showing a significance value of 0.000 < 0.05. The data shows that the majority of respondents (73.7%) have a good quality of life. There is correlation between family support with stroke incidence in the Bandung, because statistical test results showing a significance value of 0.001 < 0.05